DOWN SYNDROME: ETIOLOGY, PATHOGENESIS AND PREVENTION (International journal of medical sciences, 2025)
Down syndrome (DS) is a congenital genetic condition characterized by complete or partial trisomy of chromosome 21, accompanied by varying degrees of intellectual disability, congenital malformations of various systems, and additional health problems that affect life expectancy. The article analyzes current information on the etiology of the disease (chromosomal mechanisms: complete trisomy, mosaic and translocation forms), molecular pathogenesis (gene dosage effects and some key genes), clinical features, prenatal diagnostic methods and effective preventive measures (genetic counseling, screening and diagnostic strategies). At the same time, recommendations are given that are relevant to the context of literature and practice in Uzbekistan.